Dearomatization drives complexity generation in freshwater organic matter - Li, Siyu; Harir, Mourad; Bastviken, David; Schmitt-Kopplin, Philippe; Gonsior, Michael; Enrich-Prast, Alex; Valle, Juliana; Hertkorn, Norbert (Nature (London), 2024)
Dissolved organic matter (DOM) is one of the most complex, dynamic and abundant sources of organic carbon, but its chemical reactivity remains uncertain 1 – 3 . Greater insights into DOM structural features could facilitate understanding its synthesis, turnover and processing in the global carbon cycle 4 , 5 . Here we use complementary multiplicity-edited 13 C nuclear magnetic resonance (NMR) spectra to quantify key substructures assembling the carbon skeletons of DOM from four main Amazon rivers and two mid-size Swedish boreal lakes. We find that one type of reaction mechanism, oxidative dearomatization (ODA), widely used in organic synthetic chemistry to create natural product scaffolds 6 – 10 , is probably a key driver for generating structural diversity during processing of DOM that are rich in suitable polyphenolic precursor molecules. Our data suggest a high abundance of tetrahedral quaternary carbons bound to one oxygen and three carbon atoms (OC q C 3 units). These units are rare in common biomolecules but could be readily produced by ODA of lignin-derived and tannin-derived polyphenols. Tautomerization of (poly)phenols by ODA creates non-planar cyclohexadienones, which are subject to immediate and parallel cycloadditions. This combination leads to a proliferation of structural diversity of DOM compounds from early stages of DOM processing, with an increase in oxygenated aliphatic structures. Overall, we propose that ODA is a key reaction mechanism for complexity acceleration in the processing of DOM molecules, creation of new oxygenated aliphatic molecules and that it could be prevalent in nature. Using complementary multiplicity-edited 13 C nuclear magnetic resonance spectra, oxidative dearomatization is shown to be a key driver for generating structural diversity during processing of dissolved organic matter and the data also suggest high abundance of OC q C 3 units.